Characterization and stability of selected biochars and effect of their application on soil physical properties and corn growth - Mohialdeen, Abulrazzaq Huda (2015)
The intentional amendment of soil with biochar is offering a new strategy for improving soil fertility and sequestering atmospheric CO2. Nonetheless, the characteristics of biochars vary with their different conditions and pyrolysis techniques to improve the physical properties and carbon sequestration of soil as to enhance plants growth. This research is to prove that biochar considers as a stable product that can be produced from feedstock pyrolysis by one of the available bioenergy production techniques. The study aimed to improve the understanding of how adding biochar applications and the pyrolysis of native feedstock to soil can be utilized to improve carbon stability, soil physical properties, and soil fertility in Malaysia. Adding biochar to soils has established a variety of advantages that vary according to the type of the feedstock as the types of the utilized pyrolysis conditions in biochar production. An emphasis was placed on understanding how both of biomass material and production conditions of the pyrolysis process can influence biochar characteristics, and what effects can result from adding different rate of the amendment biochar on soil and plant growth. Three kinds of primary biochar were used, namely, empty fruit bunch biochar (EFB), wood biochar (WB), and rice husk biochar (RHB). EFB and WB were produced by slow pyrolysis method, whereas RHB was produced by the gasification. Four sets of experiments were conducted. In the first set of experiments, the influences of slow pyrolysis and gasification on biochars were examined independently. The physicochemical structure of the produced biochars was characterized with various analytical techniques including FTIR, XRD, SEM, HPLC, and BET surface area analysis. In the second and third sets of experiments, a field study had been carried out to evaluate the effect of the biochar incorporation on soil in regards to the carbon stability and soil physical properties, the final set was carried out in a shade house to evaluate the effect of adding biochars treatment on plants’ heights and dry shoot growth. The results revealed the presence of a very labile C-fraction in RHB with a very small decay constant K3. Fourier transform infrared spectroscopy and X-ray diffraction showed three phases of the biochar, from the microcrystalline C of the labile fraction to the largely amorphous intermediate C of the unstable fraction, and finally the formation of turbostratic crystallite C in the recalcitrant fraction. Furthermore, biochar incorporation into soil has effect on soil water content and hydraulic conductivity, contributes to improve soil structure, and improved moisture characteristics, regarding to the extensive pore structures, surface characteristics, and high porosity of RHB as compared to EFB and WB. EFB30 in pot trials resulted in a highly positive effect on sweet corn growth with 50% of fertilizers; On the other hand, RHB30 did not have positive impact on the growth. Due to its labile fraction might cause microbial immobilization of soil N. It has been concluded that, RHB had a higher degree of aromaticity, greater stability, and therefore should be more recalcitrant to biological and chemical degradation. Applying biochar substances by using local materials is assessing promises of being an environmentally sound in enhancing the physical characteristics of soil and crop productivity in Malaysia.